Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

solve the following equation for the value x:?

solve the following equation for the value x: (log x^3) = log x^3

6 Answers

Relevance
  • reza
    Lv 4
    1 decade ago
    Favorite Answer

    I think you mean (logx)^3=log (x^3)

    log(x^3)=3log x

    log x=a then

    a^3=3a

    a^3-3a=0

    a(a^2-3)=0

    If a=0 then log x=0 and x=1

    If a^2-3=0 then a^2=3 and a= + or - (3sqert)

    If a=(3sqrt) then log x=(3 sqrt) and x=(base)^(3sqrt)

    If a=-(3sqrt) then logx=-(3sqrt) and x=(base)^(-3 sqrt)

  • 1 decade ago

    log x^3 = log x^3 is like saying 4 = 4. When both sides of the equation are identical, the equation is always true. It won't matter what you substitute for x.

    So the answer is "all real solutions" or "all solutions" depending on the book or teacher.

  • 1 decade ago

    Your notation is slightly confusing, but I'm going to assume that it is equivalent to log(x^3) = (log x)^3

    In this case, using a logarithmic identity gives us log(x^3) = 3*log(x)

    thus, we get 3(log x) = (log x)^3

    dividing by log x, we get 3 = (log x)^2

    take the square root to get log x = sqrt(3)

    from there, x = 10^(sqrt(3)), which is approximately 10^1.73205081 or 53.9573746

  • 1 decade ago

    (log x^3) = log x^3

    The solution is for all x > 0.

    If you mean (log x)^3 = log x^3, then

    (log x)^3 - 3log x = 0, x > 0

    log x [(log x)^2 - 3] = 0

    log x = 0, => x = 1

    log x = ±√3, => x = 10^[±√3]

  • How do you think about the answers? You can sign in to vote the answer.
  • Romy C
    Lv 5
    1 decade ago

    (log x^3) = log x^3

    log x^3 = log x^3

    but x cannot be 0 or negative since logx where x<= 0 is undefined thus,

    x>0

  • mcveay
    Lv 4
    5 years ago

    5 - 2(x-a million) = 3x - 8 => 5 + 8 = 3x + 2(x-a million) (positioned all the X's on one area) => 5 + 8 = 3x + 2x - 2 (multiply out the brackets) => 5 + 8 + 2 = 3x + 2x (pass the two over to the different area) => 15 = 5x (upload each little thing on the two facets) => x = 15/5 (divide) => x = 3

Still have questions? Get your answers by asking now.